2009
DOI: 10.1073/pnas.0809559106
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the thymic IL-7 niche in vivo

Abstract: The thymus represents the ''cradle'' for T cell development, with thymic stroma providing multiple soluble and membrane cues to developing thymocytes. Although IL-7 is recognized as an essential factor for thymopoiesis, the ''environmental niche'' of thymic IL-7 activity remains poorly characterized in vivo. Using bacterial artificial chromosome transgenic mice in which YFP is under control of IL-7 promoter, we identify a subset of thymic epithelial cells (TECs) that co-express YFP and high levels of Il7 trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
122
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(132 citation statements)
references
References 36 publications
(64 reference statements)
7
122
0
Order By: Relevance
“…Recent studies using IL-7 reporter mice revealed that, similar to the predominance of IL-17 + gd T cells in the thymus of young mice (8), the number of IL-7-expressing thymic epithelial cells was higher in neonatal and 1-2-wk-old mice than in adult mice (49). In addition to the thymus, IL-7-expressing cells were found in peripheral organs, such as abdomen, lung, skin, and intestine, where IL-17 + gd T cells were localized (50).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using IL-7 reporter mice revealed that, similar to the predominance of IL-17 + gd T cells in the thymus of young mice (8), the number of IL-7-expressing thymic epithelial cells was higher in neonatal and 1-2-wk-old mice than in adult mice (49). In addition to the thymus, IL-7-expressing cells were found in peripheral organs, such as abdomen, lung, skin, and intestine, where IL-17 + gd T cells were localized (50).…”
Section: Discussionmentioning
confidence: 99%
“…Like other related cytokines (IL-2, IL-4, IL-9, IL-15, and IL-21), IL-7 is a member of the so-called common g-chain (g c ) family (2). It is produced by many different stromal cell types, including epithelial cells of the thymus and the intestine (3)(4)(5). The receptor for IL-7 consists of a heterodimer, the IL7Ra-chain, and the g c ; the IL-7Ra-chain is also part of the receptor for the thymic stromal lymphopoietin (TSLP) cytokine, and g c is also a component of other cytokine receptors (2).…”
mentioning
confidence: 99%
“…Evidence suggests that trans-presentation of IL-15 by parenchymal cells is crucial in the development of IL-15 responsive cells such as invariant NKT cells in the thymus [23,24]. One could envisage the IL-15Ra 1 thymic stroma presenting IL-15 and working in synergy with locally expressed IL-7 [22] to promote immature thymocyte development and perhaps invariant NKT-cell development.…”
Section: Discussionmentioning
confidence: 99%
“…While IL-15 does not appear essential for thymopoiesis in mice [20,21], previous studies have shown that TEC subsets express IL-15 [22] and could ''trans-present'' IL-15/IL-15Ra complexes to developing thymocytes [23,24]. Since the bioavailability of human IL-15 in HIS mice appears limited [3], we next investigated the effect of exogenous IL-15 on human thymopoiesis in vivo.…”
Section: Effects Of Exogenous Human Il-15 Administration On Human Thymentioning
confidence: 99%
See 1 more Smart Citation